PENGENDALIAN RISKO PASCA PANEN EDAMAME PADA PROSES GRADING DI PT. MITRATANI 27 - Andrew Setiawan Rusdianto; Winda Amilia; Akhmad Taufikqul Hakim (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Post harvest risk is a condition that must be faced by agro-industry companies. PT. Mitratani 27 is an agro-industry company that produces frozen edamame. One of the postharvest risks that occurs is losses in the process grading edamame. Therefore the AHP (Analytical Hi earchy Process) method is used to identify and determine the main causes of losses in the process grading. Generally, the AHP method is a process of comparing the criteria carried out by experts, the greater the value produced, the more important the criteria that considered by experts. The results of application AHP method that a criteria with the highest value is labor (0.755) and sub criteria for worker skills (0.259). Postharvest risk control that can be done is recommendations to improvement the skills of workers grading.